PATH-37. PROGNOSTIC ROLE OF TERT PROMOTER MUTATIONS IMPROVES THE STRATIFICATION OF IDH-MUTATED LOWER GRADE GLIOMA. (11th November 2019) - Arita, Hideyuki; Matsushita, Yuko; Ohno, Makoto; Miyake, Yohei; Saito, Kuniaki; Tanaka, Shota; Nakamura, Taishi; Tamura, Kaoru; Higuchi, Fumi; Sandika, Eriel; Sabit, Hemragul; Hattori, Yasuhiko; et al.
Abstract: TERT promoter mutation is associated with 1p/19q codeletion and favorable prognosis in IDH -mutated gliomas. Prognostic and diagnostic significance of TERT promoter mutation is well-recognized in IDH -wildtype glioblastomas, but not in IDH -mutated gliomas. We investigated prognostic efficacy of TERT mutation in a cohort of 560 Japanese IDH -mutated adult gliomas. The molecular status of IDH, TERT and 1p/19q and patient clinical data including Karnofsky performance status (KPS) were collected in all cases. TERT mutations and 1p/19q codeletions were found in 303 and 285 cases, respectively. The patient cohort was divided into four groups by a combination of the 1p/19q and TERT status. The characteristics of 1p/19q intact- TERT mutated group (Astro-TERT group, n=24) were compared with those of 1p/19q intact- TERT wild (Astro-group, n=251) or 1p/19q codeleted- TERT mutated (Oligo-group, n=279) cases. Astro-TERT group with any grade showed intermediate overall survival between the Oligo-group and Astro-group although the survival differences were not statistically significant (median overall survival (OS) not reached (NR) versus NR, and 106 months, respectively. p >0.05). We further conducted subgroup analysis by adjusting KPS and WHO grade as Cox regression analysis for survival indicated the unfavorable survival impact of KPS < 90 and WHO grade IV. In the subgroup with favorable KPS (90–100) and grade II-III (n=438), The OS of Astro-TERT group (median NR) was significantly longer survival than that of Astro-group (median 120.2 months, p=0.032), and was comparable with that of the Oligo-group (median NR, p >0.05). On the other hand, OS of none of the molecular groups significantly differ in poorer KPS subgroups (p >0.05). In grade IV tumors, the OS of the Astro-TERT group (NR) was comparable with that of Astro-group (29 months, p=0.19) rather than Oligo-group (NR, p=0.051). Thus, TERT promoter status provides a valuable prognostic information for IDH -mutated grade II-III gliomas in the current molecular diagnostic system.